Feasibility of using scent-baited hair traps to monitor carnivore populations in Peninsular Malaysia - Hedges, L.; Morrant, D.S.; Campos-Arceiz, A.; Clements, G.R. (2015)
Non-invasive genetic sampling is increasingly being used for monitoring mammalian carnivore populations. However, environmental conditions in the tropics challenge researchers' ability to collect samples. We present the results of a preliminary study on the feasibility of using scent-baited hair traps for population monitoring of mammalian carnivores in Peninsular Malaysia. Stations were baited using either fatty acid scent or male cologne applied to hair traps. Video camera traps were also used to monitor carnivore reactions to the scent stations. We recorded 19 visits by seven carnivore species over 764 camera trap nights. Cheek-rubbing and scent-marking behaviour was recorded only for single individuals of two species: the Malayan tiger (Panthera tigris jacksoni) and clouded leopard (Neofelis nebulosa). This study suggests that scent-baited hair traps hold some promise for ecological issues requiring DNA analysis in Peninsular Malaysia. Additional research is needed to develop its full potential for conservation monitoring of large carnivores.